Integrating Qur’anic Values against Radicalism: An Ethnographic Study at a Boarding School - Muttaqo, Moh. Ali; Saihu, Made (Edukasi, 2025)
This research examines the integration of Qur'anic values in the curriculum of Darul Amin Salafi islamic boarding school as an effort to build contextual and inclusive anti-radicalism education. The background of the research is based on the increasing challenges of radicalism due to textual and literal religious understanding. The purpose of the research is to understand how Qur'anic values are integrated in the curriculum, the role of exemplary teachers as Living Qur'an, critical dialog space, and the relationship between pesantren and local wisdom in shaping the tolerant and anti-radicalism character of santri. This research uses a qualitative approach with ethnographic methods, through participatory observation, in-depth interviews, and documentation studies conducted over a three-month period. The results showed that Darul Amin developed a thematic tafsir-based curriculum with the value of rahmatan lil 'alamin as the main framework, as well as providing historical and social contexts for sensitive verses such as jihad. Teachers as Living Qur'an figures encourage dialogic and tolerant character learning, while open discussion spaces strengthen student's critical and inclusive attitudes. The integration of Islamic values with Dayak local wisdom has proven effective in creating social harmony and facilitating multicultural education. The implication of this research confirms the importance of pesantren as strategic institutions for deradicalization through contextual curriculum, character building, and inclusive social dialogue.